OsATX1 Interacts with Heavy Metal P1B-Type ATPases and Affects Copper Transport and Distribution. Issue 1 (12th July 2018) - Zhang, Yuanyuan; Chen, Kai; Zhao, Fang-Jie; Sun, Cuiju; Jin, Cheng; Shi, Yuheng; Sun, Yangyang; Li, Yuan; Yang, Meng; Jing, Xinyu; Luo, Jie; Lian, Xingming
Abstract : OsATX1 controls root-to-shoot translocation of copper and its delivery to developing tissues in rice by interacting with the rice heavy metal P1B-ATPases HMA4, HMA5, HMA6, and HMA9. Abstract: Copper (Cu) is an essential micronutrient for plant growth. However, the molecular mechanisms underlying Cu trafficking and distribution to different organs in rice ( Oryza sativa ) are poorly understood. Here, we report the function and role of Antioxidant Protein1 (OsATX1), a Cu chaperone in rice. Knocking out OsATX1 resulted in increased Cu concentrations in roots, whereas OsATX1 overexpression reduced root Cu concentrations but increased Cu accumulation in the shoots. At the reproductive stage, the concentrations of Cu in developing tissues, including panicles, upper nodes and internodes, younger leaf blades, and leaf sheaths of the main tiller, were increased significantly in OsATX1 -overexpressing plants and decreased in osatx1 mutants compared with the wild type. The osatx1 mutants also showed a higher Cu concentration in older leaves. Yeast two-hybrid and bimolecular fluorescence complementation assays showed that OsATX1 interacts with the rice heavy metal P1B -ATPases HMA4, HMA5, HMA6, and HMA9. These results suggest that OsATX1 may function to deliver Cu to heavy metal P1B -ATPases for Cu trafficking and distribution in order to maintain Cu homeostasis in different rice tissues. In addition, heterologous expression of OsATX1 in the yeast ( Saccharomyces cerevisiae ) cadmium-sensitive mutant Ɗ ycf1 increased the tolerance to Cu and cadmium by decreasing their respective concentrations in the transformed yeast cells. Taken together, our results indicate that OsATX1 plays an important role in facilitating root-to-shoot Cu translocation and the redistribution of Cu from old leaves to developing tissues and seeds in rice.